The Issue of the Main Character in the Novel "Kecha Va Kunduz" (Eurasian Journal of Humanities and Social Sciences, 2022)
This article analyzes the system of characters and main character in Cholpon's novel "Kecha Kunduz", as well as the writer's skill in character drawing.